The Advent of a Three-Body Problem Artificial Intelligence and Political Theologies - Douglas, Mark 1966-; Shin, Wonchul (2025)
The phrase, “political theology,” has been understood in at least three ways: to describe the political implications of various theologies, to describe a theology of politics, and to describe the theological language that funds modern secular political systems. This paper explores the way generative artificial intelligence intersects with each of those understandings, especially noting the impact of AI on actual physical and corporate bodies. It argues for closer attention to the moral concerns that are raised within each understanding and advocates for design justice as a way to push the development of AI towards supporting systems that promote the flourishing of individual and corporate bodies.
Keywords: Design Justice; Embodied Practices; Karl Schmitt; Theological Anthropologies; Liberation/Decolonial Theologies; Three-Body Problem; Political Theology; Generative Artificial Intelligence